2020
DOI: 10.1186/s40163-020-00131-8
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling community-level changes in crime trends during the COVID-19 pandemic in Chicago

Abstract: Recent studies exploiting city-level time series have shown that, around the world, several crimes declined after COVID-19 containment policies have been put in place. Using data at the community-level in Chicago, this work aims to advance our understanding on how public interventions affected criminal activities at a finer spatial scale. The analysis relies on a two-step methodology. First, it estimates the community-wise causal impact of social distancing and shelter-in-place policies adopted in Chicago via … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
139
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 73 publications
7
139
1
6
Order By: Relevance
“…While there was a demonstrable change in mobility towards the end of March, the largest impact on mobility was not observed—and then sustained—until the month of April. Changes in property crime have tended to follow the expected pattern, given the changes to mobility, and are largely consistent with studies conducted overseas and in Australia (Ashby 2020a ; Boman and Gallupe 2020 ; Borrion et al 2020 ; Campedelli et al 2020a , b ; Felson et al 2020 ; Gerell et al 2020 ; Halford et al 2020 ; Kim and Leung 2020 ; Mohler et al 2020 ; Rmandic et al 2020 ; Rosenfeld and Lopez 2020 ). In fact, it would appear that the significant reductions in crime observed in Queensland exceeded those observed in the United States, and are higher than those observed in the only other Australian studies to date (Kim and Leung 2020 ; Rmandic et al 2020 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…While there was a demonstrable change in mobility towards the end of March, the largest impact on mobility was not observed—and then sustained—until the month of April. Changes in property crime have tended to follow the expected pattern, given the changes to mobility, and are largely consistent with studies conducted overseas and in Australia (Ashby 2020a ; Boman and Gallupe 2020 ; Borrion et al 2020 ; Campedelli et al 2020a , b ; Felson et al 2020 ; Gerell et al 2020 ; Halford et al 2020 ; Kim and Leung 2020 ; Mohler et al 2020 ; Rmandic et al 2020 ; Rosenfeld and Lopez 2020 ). In fact, it would appear that the significant reductions in crime observed in Queensland exceeded those observed in the United States, and are higher than those observed in the only other Australian studies to date (Kim and Leung 2020 ; Rmandic et al 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…Property crimes, including shoplifting and thefts, decreased, as did crime overall, and these trends were amplified during the period of more stringent measures. In a follow-up paper, Campedelli et al ( 2020b ) assessed how COVID-19-related containment policies were associated with different crime types at the community-level in Chicago and found that changes in crime trends differed across both communities and crime types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent working paper, McDonald and Balkin (2020) simply report changes in crime rates in four major U.S. cities relative to the prior year without any standard errors. Other papers focus on specific jurisdictions, including Chicago ( Campedelli et al, 2020b ), Los Angeles ( Campedelli et al, 2020a ) Queensland, Australia ( Payne and Morgan, 2020a , Payne and Morgan, 2020b ), and Lancashire, UK ( Halford et al, 2020 ). These analyses report mixed results from little change in Queensland to substantial declines in crime in Los Angeles.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies took no account of other socioeconomic factors affecting occurrence of crime. Although a recent study focused on spatial variations in crime trend, the influential factors fail to account for the extent of COVID-19 infection [17]. To abridge the research gaps, we investigated the spatial association of COVID-19 infection rate and crime rates after controlling for socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%